Projecting History Honestly: An Interview with Lawrence Hill - Sagawa, Jessie (Studies in Canadian Literature, 2008)
Lawrence Hill discusses the links between his family’s history of slavery and his interest in the history of the African slave trade in general, an interest that culminated in his celebrated novel, The Book of Negroes (2007). He examines central themes in his fiction, including identity and historicity, all the while emphasizing that we cannot ignore that which is disturbing in our past. While certain parallels exist between the lives of his past and present relations and those of his characters, he views these correspondences merely as starting points from which to develop his fiction. Finally, he discusses his historical sources for The Book of Negroes.